2023
DOI: 10.1155/2023/3427151
|View full text |Cite
|
Sign up to set email alerts
|

Single Cone Obturation versus Cold Lateral Compaction Techniques with Bioceramic and Resin Sealers: Quality of Obturation and Push-Out Bond Strength

Abstract: Objectives. This study compared the obturation quality and push-out bond strength of single cone obturation (SCO) and cold lateral compaction (CLC) with AH-Plus and Sure Seal Root (SSR). Materials and Methods. This in vitro experimental study was conducted on 88 single-rootedsingle-canal teeth with straight roots that were randomly divided into four groups (n = 22). All teeth were decoronated and underwent cleaning and shaping. Obturation was performed with AH-Plus and SCO technique in group 1 (SAH), AH-Plus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…Consistent with prior studies, we observed a substantial reduction in PAI scores following endodontic treatment in both groups [56,57]. In line with other investigations, tooth mobility and pain at the intervention site were significantly reduced after treatment across both sealers [58,59].…”
Section: Analysis Of Results and Literature Findingssupporting
confidence: 92%
“…Consistent with prior studies, we observed a substantial reduction in PAI scores following endodontic treatment in both groups [56,57]. In line with other investigations, tooth mobility and pain at the intervention site were significantly reduced after treatment across both sealers [58,59].…”
Section: Analysis Of Results and Literature Findingssupporting
confidence: 92%
“…Comprehensive knowledge regarding the prevalence and variations of this anatomy can help reduce the occurrence of endodontic treatment failures in these teeth. Recent research has examined endodontic errors and anatomical characteristics of mandibular molars in an Iranian population [19]. However, information on C-shaped canals in this population is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT was used in this study because it does not require sectioning or damaging teeth and can be applied clinically [21]. We analyzed existing CBCT scans taken for other diagnostic or treatment purposes, which provided an excellent noninvasive means of obtaining anatomical information [17,19].…”
Section: Scanningmentioning
confidence: 99%
See 2 more Smart Citations